Bioactivities of EF24, a Novel Curcumin Analog: A Review - He, Yonghan; Li, Wen; Hu, Guangrong; Sun, Hui; Kong, Qingpeng (Frontiers in Oncology, 2018)
Curcumin is an attractive agent due to its multiple bioactivities. However, the low oral bioavailability and efficacy profile hinders its clinical application. To improve the bioavailability, many analogs of curcumin have been developed, among which EF24 is an excellent representative. EF24 has enhanced bioavailability over curcumin and shows more potent bioactivity, including anti-cancer, anti-inflammatory and anti-bacterial. EF24 inhibits tumor growth by inducing cell cycle arrest and apoptosis, mainly through its inhibitory effect on the nuclear factor kappa B (NF-κB) pathway and by regulating key genes through microRNA (miRNA) or the proteosomal pathway. Based on the current structure, more potent EF24 analogs have been designed and synthesized. However, some roles of EF24 remain unclear, such as whether it induces or inhibits reactive oxygen species (ROS) production and whether it stimulates or inhibits the mitogen activated kinase-like protein (MAPK) pathway. This review summarizes the known biological and pharmacological activities and mechanisms of action of EF24.